Regime e sistemas de controle das cheias do baixo Ivaí e cartografia das áreas inundáveis - Douhi, Nelson (2013)
The study presented in this essay corresponds to a survey of hydrogeomorphological conditions of the Ivai River, in a stretch of its alluvial plain, the identification of the systems that control the floods and the spatial representations of the floods regarding the rain levels that are more expressive. The information that served as basis of this essay are results of bibliographic research in specific literature, also in studies of cases, made in the watersheds of the rivers Ivai and Paraná and in loco studies, where the anthropogenic interventions in the alluvial plain, the limits of the floods, besides obtaining the information about the dynamics and the flood implications to riparian people. The weather characteristics of the watershed were evaluated as well as the hydrological behavior of the river, regarding the historical basis of the rain level in the watershed and the variation of the rain level in the stations of Novo Porto Taquara (Ivai River) and Porto Caiuá (Paraná river). Next to the junction of the Ivai river and Paraná river, a fluviometric ruler was installed, objecting to evaluate the occurrence of the flows control in the confluence and their implications in the flood occurrences. The natural and artificial controls that have influence in the floods were also considered. The spatial representation of the floods was based in the interpretation of images of satellites and information collected in field, for example flood marks sediments that are deposited and the confirmations of their limits with the GPS. The analysis made indicates that the floods have their occurrence associated to the pluvial events of bigger intensity and the influence of control systems. It was verified that the stay time of the floods is short and have no influence from the seasonality, characterizing a reflex of the quick answers that the watershed present according to their morphological characteristics, soil and geological. Considering the annual occurrences, there is a regularity, though years without flooding occurring, making it more difficult to build the connectivity of their environment. The inundated areas with bigger recurrence don't add great extensions and loss, however, the ones associated to bigger magnitudes, although represent inundated areas and bigger losses, are less frequent.